Redes globales y contextos locales: interacciones e interpenetraciones. - Rodríguez, Francisco (Espacio Abierto, 1970)
Globalization is the universalizing of the capitalism in its later phase, not only in relation to capital markets and technological processes, but, and this is the most important, as a lifestyle based on consumption. But the consumption that constitutes the basis for implanting this process is not fundamentally one of material products, but of signs, symbols and images. Universalism of the market of signs and symbols that globalization represents, operates on the basis of the pulverization of symbolic memory that makes reference to imaginary collectives expressed in terms of the national regional and local reality. The worlds of life and the subjectivities that support the structures of the traditional and modern systems, are colonized by communicational devices that produce de-socialization and de-culturalization when they dis-associate culture and society in the first place, and then, society and technical- instrumental rationality, in second place. Nevertheless, globalization seen in the universalism of the subjective market, is reacted to by diverse manifestations of socio-cultural particularities and multiple resistance reactions. These particularities are expressed in varied forms of negotiated identities in relation to local cultures that adopt the symbolism of global nets in order to continue subsisting.